OPTIMIZATION AND ANALYSIS OF AN INTERIOR PERMANENT MAGNET SYNCHRONOUS MOTOR - Sarac, Vasilija (Journal of Energy Technology, 2025)
This paper aims to optimize an interior permanent magnet synchronous motor and analyze the operating characteristics of optimized models compared to the starting model. The optimization is done by optometric analysis, i.e., four motor parameters are selected and varied within certain boundaries, allowing new motor models to be obtained from each combination of these parameters. The best candidates are selected, i.e., models concerning the efficiency and cogging torque. The optimized models have improved efficiency and cogging torque compared to the starting model.